Cultural capital, curriculum policy and teaching Latin - Gatley, Jane (British educational research journal, 2023)
Latin is currently being trialled as a subject in 40 state secondary schools in England. This paper focuses on one of the justifications of this trial: that teaching Latin in state secondary schools provides students with cultural capital which in turn counters social injustice. By taking the example of Latin as a starting point, I reach two conclusions about cultural capital. The first is that providing students with cultural capital can be good for some individuals, and so justified on a case‐by‐case basis depending on context. However, this justification does not hold for curriculum policy making. My second conclusion is that in the long term, pursuing cultural capital as part of curriculum policy exacerbates the social injustices it purports to address. Wherever an activity is introduced for the sake of cultural capital rather than its educational value, educationally valuable activities risk being pushed off the curriculum, potentially degrading the educational value of the curriculum. In the case of teaching Latin, it may provide benefits to particular students, but as part of curriculum policy it risks exacerbating social injustices and undermining the educational value of school curricula. Going beyond the place of Latin on the curriculum, I argue that all appeals to cultural capital provide a poor basis for curriculum policy making.